Pedicled buccal fat pad flap for intraoral malignant defects: A series of 29 cases - Chakrabarti, Jayanta (Medknow Publications, 2009)
A buccal fat pad (BFP) as a flap for reconstruction of defects in the oral cavity has been described for a variety of benign conditions. We describe the indications, advantages, and complications of the BFP flap and report our clinical experience with the flap for intraoral reconstruction after tumor removal. From 2005 to 2008, we analyzed 29 patients in the age range of 32 to 82 years old who underwent a pedicled BFP flap reconstruction for oral defects after intraoral tumor removal. Postoperative wound healing and complications including any recurrence was followed-up prospectively. Most of the patients had an uneventful immediate postoperative period with signs of buccal fat pad epithelialization by the end of the first week and complete epithelialization at the end of the first month. On continued follow-up, a linear band of fibrous tissue under the epithelialized mucosa replaced the once reconstructed buccal fat pad. Three patients had varying degrees of hemorrhage: one of them had hematoma that healed with severe fibrosis and of the remaining two, one had a partial flap loss and one had a complete flap loss. Judicious use of buccal fat pad reconstruction offers a simple, convenient, and reliable way to reconstruct small to medium defects of the oral cavity with low morbidity, even in older patients who would not be able to tolerate time-consuming flap reconstruction procedures.